Epidemiology and Pathogenesis of Nasal NK/T-Cell Lymphoma: A Mini-Review - Katsuyuki Aozasa; Mona A. A. Zaki (The Scientific World Journal)
Nasal NK/T-cell lymphoma (NKTCL) frequently presents with necrotic, granulomatous lesions in the upper respiratory tract, and usually shows a highly aggressive clinical course. Thus, it was initially included in the clinical condition of lethal midline granuloma. Recently, the disease has been recognized as a neoplastic proliferation of NK/T cells. The disease is much more frequent in Asian and Latin American countries than in Western countries, and is universally associated with Epstein-Barr virus (EBV) infection. Analyses of gene mutations, especially p53 and c-kit, revealed the different frequencies by district. Abnormalities of other genes have also been reported. Case-control studies showed that the exposure to pesticides and chemical solvents could be causative of NKTCL. Further studies including HLA antigen typing of patients is necessary to further clarify the disease mechanism.